2017
DOI: 10.3389/fnhum.2017.00611
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Explicit Evaluation on Neural Connectivity Related to Listening to Unfamiliar Music

Abstract: People can experience different emotions when listening to music. A growing number of studies have investigated the brain structures and neural connectivities associated with perceived emotions. However, very little is known about the effect of an explicit act of judgment on the neural processing of emotionally-valenced music. In this study, we adopted the novel consensus clustering paradigm, called binarisation of consensus partition matrices (Bi-CoPaM), to study whether and how the conscious aesthetic evalua… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
15
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
2
2

Relationship

2
8

Authors

Journals

citations
Cited by 27 publications
(17 citation statements)
references
References 78 publications
(116 reference statements)
1
15
0
1
Order By: Relevance
“…This sheds new light on the role of sensory cortices in emotion and suggests that the auditory association cortex not only processes perceptual information, but also influences emotional processes as a function of perceptual input (the neural origins of the appraisal processes that give rise to such influence remain to be specified-possible candidates are brainstem, thalamus, auditory cortex, and higher-order cortices). Consistent with these results, a study by Liu et al (2017) reported auditory-limbic functional connectivity during listening to pop/rock songs, and a study by Salimpoor et al (2013) reported increased functional connectivity between the (right) auditory cortex and the ventral striatum/nucleus accumbens with increasing reward value of music (as measured by the amount of money participants were willing to spend on the music they heard in the fMRI scanner), thus predicting reward value. Correspondingly, functional connectivity between the auditory cortex and the nucleus accumbens is reduced in individuals with ''specific musical anhedonia,'' whereas individuals with average or greater-than-average reward sensitivity to music show enhanced connectivity between these structures.…”
Section: Neural Correlatessupporting
confidence: 52%
“…This sheds new light on the role of sensory cortices in emotion and suggests that the auditory association cortex not only processes perceptual information, but also influences emotional processes as a function of perceptual input (the neural origins of the appraisal processes that give rise to such influence remain to be specified-possible candidates are brainstem, thalamus, auditory cortex, and higher-order cortices). Consistent with these results, a study by Liu et al (2017) reported auditory-limbic functional connectivity during listening to pop/rock songs, and a study by Salimpoor et al (2013) reported increased functional connectivity between the (right) auditory cortex and the ventral striatum/nucleus accumbens with increasing reward value of music (as measured by the amount of money participants were willing to spend on the music they heard in the fMRI scanner), thus predicting reward value. Correspondingly, functional connectivity between the auditory cortex and the nucleus accumbens is reduced in individuals with ''specific musical anhedonia,'' whereas individuals with average or greater-than-average reward sensitivity to music show enhanced connectivity between these structures.…”
Section: Neural Correlatessupporting
confidence: 52%
“…Another cluster comprised higher-order structures involved in visual processing (cuneus, lingual gyrus, middle, inferior and superior occipital gyri and fusiform gyrus). It can thus be proposed that the subjective psychological state that can be captured with first-person measures is an important predictor of the emotion-related brain processes during listening to music [ 36 ]. Future studies could also answer the unsolved question of whether and how repeated aesthetic listening to music can shape neural connectivity ( Figure 2 ).…”
Section: Brain Connections During the Experience Of Musical Rewardmentioning
confidence: 99%
“…Unhelpful listening habits are not conducive to regulating negative emotions; only the effective strategies of listening to music, such as self-chosen music [ 20 ], self-awareness, and conscious music listening choices [ 22 ], can help regulate daily emotions as well as induced negative emotions. Effective music listening can reduce negative emotional experiences, improve psychological health [ 10 , 21 , 23 , 24 , 25 , 26 , 27 ], and enhance cognitive functions [ 10 , 20 , 21 ].…”
Section: Introductionmentioning
confidence: 99%